The landscape painter's workbook essential studies in shape, composition, and color - Albala, Mitchell, 1956- (For artists, 2021)
"The Landscape Painter's Workbook takes a modern approach to the time-honored techniques and essential elements of landscape painting, from accomplished artist, veteran art instructor, and established author Mitchell Albala"--